Middle–Late Holocene paleoenvironmental reconstruction of a Salado River sector - Samborombón Bay using benthic foraminifera - Ballesteros Prada, Angélica María (2024)
The effect of Holocene sea-level changes and their impact on coastal environments have been well-preserved in different places worldwide. Several studies along the Argentine coastal margin have contributed to understanding the extent and magnitude of the marine ingression occurred during the Mid-Holocene Highstand and its effect on the ecosystem. In this research, we present a benthic foraminiferal fauna analysis of an outcrop located in Samborombón Bay - Argentina, with the aim to evaluate the maximum extent of the Holocene marine transgression in the middle zone of the bay. Along the sedimentary section, species Cribroelphidium poeyanum, Cribroelphidium gunteri, Ammonia tepida, Elphidium galvestonense and Ammonia parkinsoniana were the most representative species, while Quinqueloculina milletti and Haynesina germanica were represented in less proportion in some levels. This assemblage indicates that the study area represents a marine marginal environment with brackish conditions between 6261 –5919 cal. years BP. and 1725–1511 cal. years BP. However, the diversity and abundance of the foraminiferal fauna reveals the transition from a shallow estuarine environment (6261–5919 cal. years BP) to a brackish marsh environment with floodable depressions and greater freshwater influence (1725–1511 cal. years BP). These changes are related not only to regressive and transgressive events that occurred during the Holocene, but also to the climatic, oceanographic, hydrological, and geomorphological characteristics of the middle zone of the Samborombón Bay.